Home Appliance Control with Publish Subscribe in Social Media - Sabriansyah Rizqika Akbar; Eko Setiawan; Achmad Basuki (Universitas Ahmad Dahlan, 2015)
Nowadays, Internet social media has enriched the way people to communicate and interact each other. Will it be possible for people to interact with their home appliances around? This paper proposes a new approach in smart home system that made possible for people to remotely interact with their appliances using social media networks. In this paper, we present a smart home prototype system that leverages Twitter’s Application Program Interface (API) to remotely control home appliances over the Internet. Experiment results showed that the system immediately responds to remote commands sent over a social media account to control home appliances. The system responds the command in 3672.96 ms. Publish-subscribe method work better in mass announcement communication system. Home system could notice all householders in less than 6 s independenly from number of householder. Our proposed method gives alternative solution to build reliable, fast and simple control method.